Postpartum experiences in relation to childbirth assisted by obstetric nurses (Research, Society and Development, 2021)
The aim of the study was to analyze the experience of the puerperal woman regarding humanized delivery performed by obstetric nurses. It was a descriptive exploratory research with a qualitative approach, with a survey of the number of puerperal women, who had vaginal births attended by obstetric nurses at a Maternity School located in the countryside of Rio de Janeiro, in the period between September 2018 to September 2019. A final sample of 13 postpartum women was obtained. The interviews and reports were analyzed and categorized. The characterization of the study sample was composed by the predominance of women in the age group between 18 and 36 years old, mixed race, single, multiparous and with incomplete high school. From the analysis and reports of the parturient women, four categories of study analysis were selected, namely: 1) Welcoming the pregnant woman as a differential in the assistance of the obstetric nurse; 2) Assistance to labor and technologies used for pain relief; 3) Birth assisted by the obstetric nurse and the golden hour as a bond between the binomial and 4) The perception and experience of the puerperal woman in relation to humanized childbirth. It was concluded with the research that the experience lived by the puerperal woman regarding the humanized delivery assisted by the obstetric nurse maintains the autonomy, freedom and uniqueness of the woman during the parturition process and guaranteeing the humanized labor.